SMART HOUSE OPPORTUNITIES IN PRESENT - Šperga, Āris; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGIES. Proceedings of the Students International Scientific and Practical Conference, 2021)
The author performed an analysis why testing is important for e-commerce application. The work contains basic information about testing, software development and e-commerce.